PENGARUH PERTUMBUHAN PERUSAHAAN, FINANCIAL DISTRESS, RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP OPINI AUDIT GOING CONCERN - Ni Wayan Maidayanti (Hita Akuntansi dan Keuangan, 2021)
Audit, going concern, produced by the auditor in order to provide assurance whether an entity is able to maintain its survival. This study aims to examine the effect of company growth, financial distress, liquidity ratio, and solvability ratio toward going concern audit opinion for manufacturing sector companie that was listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2019. With populations of 168 companies. The data was obtained from the official page of the Indonesia Stock Exchange (IDX). Determination of the number of samples by using purposive sampling method, in, order, to obtain a sample of 62 companies. In this study, hypothesis testing was done by using logistic regression analysis techniques with a significance level of 5%. The results showed that financial distress affected positive and significant towards going concern audit opinion, while company growth, liquidity ratio and solvability ratio do not affected significant toward going concern audit opinion.